ANALISIS TERAPI ANEMIA PADA PASIEN GAGAL GINJAL KRONIK DI RSUD Dr. DRADJAT PRAWIRANEGARA TAHUN 2022 - Insani, Nurul; Zulfiani, Nia; Yusransyah, Yusransyah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2024)
AbstractUnder normal circumstances, 90% of the kidneys produce the hormone erythropoietin which has the function of stimulating the spinal cord to produce red blood cells, so that when kidney function decreases, there is a decrease in the production of the hormone erythropoietin which causes the formation of erythrocytes to be disrupted, resulting in a decrease in hemoglobin levels or anemia. The aim of this study was to determine the therapy of anemia in patients with chronic kidney failure undergoing hemodialysis and to determine the results of anemia therapy in patients with chronic renal failure undergoing hemodialysis at RSUD Dr. Dradjat Prawiranegara Year 2022. The research was conducted using a retrospective descriptive method by looking at the medical record data of chronic kidney failure patients undergoing hemodialysis who were receiving anemia therapy. The sample in this study amounted to 80 patients. The data were then analyzed descriptively regarding the analysis of anemia therapy in hemodialysis chronic kidney failure patients. The results showed that the hemodialysis hemoglobin level examination found an average of 8.8 g/dL and was included in the range below the normal value of hemoglobin levels. The most use of anemia drug therapy in 2022 for mono therapy is the most PRC Transfusion of 1 mg Folic Acid combination in 39 patients (48.8%). Furthermore, in the combination therapy of anemia with Blood Supplementary Tablets combined with Folic Acid 1 mg in 17 patients (21.3%) and the use of folic acid 1 mg in 24 patients (30.0%).Keywords: Anemia, Chronic Kidney Failure, Hemodialysis, RSUD Dr. Dradjat Prawiranegara.